Integrating Emotional and Spiritual Quotient (ESQ) with Prophetic Values in Human Resource Development - Ikhwan, Afiful; Rohmad, Ali; Tobroni,; Zukhrufin, Fina Kholij (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This study aims to analyse the application of prophetic values in human resource development based on Emotional and Spiritual Quotient (ESQ), with the goal of fostering a culture of integrity within Indonesian Islamic educational institutions. Employing an interpretive paradigm and a qualitative case study approach, the research was conducted purposively at a madrasah ‘āliyah (Islamic senior high school). Data were collected through in-depth interviews to explore the conceptualisation and implementation of prophetic values in the context of human resource development. The findings reveal four key processes: (1) understanding and internalising the ethical principles of educators; (2) human resource development through the assessment of social needs, structured coaching programs, expert-led workshops, ESQ evaluation, and performance enhancement of team members; (3) cultivating a culture of commitment, values, and integrity to support a productive and value-based work environment; and (4) conducting training and coaching to enhance competencies, transform paradigms, and promote a worship-oriented (mu‘āmalah) approach to professional duties, aimed at building resilient educational institutions capable of responding to global challenges. This study contributes to the development of prophetic-based human resource strategies by emphasising innovation in coaching practices grounded in fairness, transparency, faith, and accountability.